Persuasion - Mitchell, Julian, 1935-; Firbank, Ann.; Marshall, Bryan, 1938-; Baker, Howard, 1932-1993.; Spencer, Marian; Austen, Jane, 1775-1817.; BBC Video (Firm); Warner Home Video (Firm) ([S.l.] : BBC Video ; Burbank, CA : Warner Home Video, 2004)
Eight years after Anne Elliot turned down Captain Wentworth's proposal of marriage, they meet again. Ann now recognizes the false values that persuaded her to reject Captain Wentworth, but his heart seems set upon the youth and beauty of the impetuous Louisa Musgrove.
DVD, full screen (4:3) presentation.
Closed-captioned for the hearing-impaired.
Ann Firbank, Bryan Marshall, Marian Spencer, Basil Dignam, Valerie Gearon.
Film cameraman, David Wood; editor, Stan Challis; musical arranger, Steven Hancock; designer, Peter Phillips.
Originally produced for television broadcast in 1971.
A foreign television mini-series (Great Britain).
Keywords: Young women -- England -- Drama; Television mini-series.; Films for the hearing impaired; England -- Social life and customs -- 19th century -- Drama